Desakralisasi Nilai-Nilai Qurani dalam Tradisi Tasyakkur Khataman Masyarakat Kecamatan Pragaan - Aziz, Abdul (Medan Resource Center, 2023)
The traditional tasyakkur khataman event procession typically occurs at night, though occasionally during the day in certain villages. It commences with the recitation of Juz 'Amma from the Qur'an followed by a festival featuring drumband music, held in a lavish setting to highlight the significance of the Qur'an khataman activities. The leader of the procession, typically mounted on a horse adorned extravagantly by the committee, symbolizes the grandeur of the event. The study focuses on the tasyakkur khataman tradition in Pragaan Daya and Pragaan Laok villages, aiming to understand its evolution over time and the desacralization of Qur'anic values within the community. Employing qualitative field research with a case study approach, data was gathered through interviews, observations, and documentation. Findings revealed the tradition's historical continuity over four distinct periods and identified five areas of Qur'anic values desacralization.